Comparison of RT.PCR and ELISA Methods in the Diagnosis of Human Cytomegalovirus in Kidney Transplant Patients - Fatemeh Bali Chalandar; Haniyeh Bashi Zadeh Fakhar; Fatemeh Rezaei (Journal of Medical Bacteriology)
Background:   In kidney transplant recipients prone to infections like cytomegalovirus (CMV), a vital need for an accurate diagnostic method is evident. This study at Khorshid Laboratory in Tehran rigorously compares real-time PCR (RT-PCR) and enzyme-linked immunosorbent assay (ELISA) for CMV detection in transplant patients. Methods:   In January to March 1400, 70 kidney transplant recipients were assessed for CMV DNA using RT-PCR and concurrent ELISA tests, with statistical analysis aided by SPSS. Results:   In kidney transplant patients (average age: 49.40 ± 13.64 years), 4.3% tested positive for CMV via PCR. Strong correlation between serological and molecular methods. IgG and IgM antibody detection both showed high sensitivity and specificity, advocating for efficient CMV diagnosis at Khorshid Laboratory, Tehran. Conclusion:   This study emphasizes the need for a quick and efficient CMV diagnostic approach in kidney transplant patients. The strong correlation between molecular and serological methods favors using the faster RT-PCR method, crucial for timely management, especially with the increasing age-related CMV incidence. The findings strongly recommend RT-PCR integration for enhanced sensitivity in kidney transplant patients at Khorshid Laboratory, Tehran.